Caracol Channel's (Colombia) Television Viewers Protection Office - Pérez, Amparo (2022)
In the following text, Amparo Pérez gives an account of the singularities which define her job as head of the Television Viewers Protection Office of Colombia's Caracol Channel. Pérez recognizes that her work is oriented towards the principles of impartiality, separation between information and opinion, respect for plurality in any of its forms, respect for honor; youth, infancy and family protection, respect for equality, preeminence of public, media's transparency and social responsability.